# Simplify -2 1/6. - (-7 1/3 )a) -5 1/6b) -9 3/6c) 9 3/6d) 5 1/6

## Answers

d

Step-by-step explanation:

[tex]-2\frac{1}{6}- (-7\frac{1}{3})=-2\frac{1}{6} + 7\frac{1}{3}\\\\[/tex]

[tex]=\frac{-13}{6} + \frac{22}{3}\\\\=\frac{-13}{6} + \frac{22*2}{3*2}\\\\=\frac{-13}{6} + \frac{44}{6}\\\\=\frac{-13+44}{6} \\\\= \frac{31}{6}\\\\=5\frac{1}{6}[/tex]

pathetic how you comment bs under questions on here and expect the same people to help you answer questions, grow up.

1) (-7)3

2) PEMDAS; simplify (5-3)

3) 5^3, 5x5x5 and 125

4) -8^4

5) 36

6) 7

7) -100

8) 30

There ya go! Pretty sure they're all right!

The answers are solved below.

Step-by-step explanation:

we have to solve the given expressions

Part A: The expression (-7)(-7)(-7)

[tex](-7)(-7)(-7)=(-1)^37^3[/tex]

Option 3 is correct

Part B: [tex]2(5 - 3)^2 + 6^2[/tex]

First step to solve the above expression is to simplify (5-3) by BODMAS rule then to square the simplification.

Option 3 is correct.

Part C: To choose the expression "five to the third power"

"five to the third power" is

[tex]5^3=5.5.5=125[/tex]

All 3 represents the expression "five to the third power"

Option 1,3,4 are correct.

Part D: The expression -8 · -8 · -8 · -8

The above expression can be written as

[tex](-8)^4[/tex]

Option 2 is correct

Part E: [tex]\text{The value of } -6^2[/tex]

[tex]-6^2=-(6\times 6)=-36[/tex]

Option 1 is correct

Part F: [tex]\text{The value of } |5| - 4(3^2 - 2)[/tex]

[tex]|5| - 4(3^2 - 2)=5-4(9-2)=5-4(7)=5-28=-23[/tex]

Option 4 is correct.

Part G: Evaluate [tex]\frac{8}{ -2}\times 4^2 + 9[/tex]

[tex]\frac{8}{ -2}\times 4^2 + 9=-4\times 16+9=-64+9=-55{ [/tex]

Option 2 is correct.

Part H: Simplify [tex]-5^2 + 8|-1| + (-3)[/tex]

[tex]-5^2 + 8|-1| + (-3)=-25+8-3=-17-3=-20[/tex]

Option 3 is correct.